Political Ecology and Alternation Pedagogy: possible dialogues for a new rural extension - Almeida Frazão, Gabriel; Thurler Dália, Jaqueline de Moraes (Universidade Federal Rural do Rio de Janeiro, 2016)
This article has as an objective present the Pedagogy of Alternation as a concrete possibility of education consistent with the concerns of a sustainable development, of conscious management, respectful to the nature and traditional knowledges of country man, consistent with the proposal of Politic Ecology for the construction of a new rural extension. With this purpose, the implantation and the expansion of the Familiar Training Centers by Alternation (CEFFAs, Centro Familiares de Formação por Alternância) in Brazil and in Argentina and their formation proposals, focusing mainly, in what refers to one of its basis, the concept of "development of the midst". This one for being malleable enabled the maintenance and the effectivation of this educational model in the last decades, even beneath contexts of political repression, in Latin America, adapting to the concepts of rural extension in different contexts.